Short‐term feeding of a ketogenic diet induces more severe hepatic insulin resistance than an obesogenic high‐fat diet. (8th August 2018) - Grandl, Gerald; Straub, Leon; Rudigier, Carla; Arnold, Myrtha; Wueest, Stephan; Konrad, Daniel; Wolfrum, Christian
Abstract : Key points: A ketogenic diet is known to lead to weight loss and is considered metabolically healthy; however there are conflicting reports on its effect on hepatic insulin sensitivity. KD fed animals appear metabolically healthy in the fasted state after 3 days of dietary challenge, whereas obesogenic high‐fat diet (HFD) fed animals show elevated insulin levels. A glucose challenge reveals that both KD and HFD fed animals are glucose intolerant. Glucose intolerance correlates with increased lipid oxidation and lower respiratory exchange ratio (RER); however, all animals respond to glucose injection with an increase in RER. Hyperinsulinaemic–euglycaemic clamps with double tracer show that the effect of KD is a result of hepatic insulin resistance and increased glucose output but not impaired glucose clearance or tissue glucose uptake in other tissues. Abstract: Despite being a relevant healthcare issue and heavily investigated, the aetiology of type 2 diabetes (T2D) is still incompletely understood. It is well established that increased endogenous glucose production (EGP) leads to a progressive increase in glucose levels, causing insulin resistance and eventual loss of glucose homeostasis. The consumption of high carbohydrate, high‐fat, western style diet (HFD) is linked to the development of T2D and obesity, whereas the consumption of a low carbohydrate, high‐fat, ketogenic diet (KD) is considered healthy. However, several days of carbohydrate restriction are known to cause selective hepatic insulin resistance. In the present study, we compare the effects of short‐term HFD and KD feeding on glucose homeostasis in mice. We show that, even though KD fed animals appear to be healthy in the fasted state, they exhibit decreased glucose tolerance to a greater extent than HFD fed animals. Furthermore, we show that this effect originates from blunted suppression of hepatic glucose production by insulin, rather than impaired glucose clearance and tissue glucose uptake. These data suggest that the early effects of HFD consumption on EGP may be part of a normal physiological response to increased lipid intake and oxidation, and that systemic insulin resistance results from the addition of dietary glucose to EGP‐derived glucose. Key points: A ketogenic diet is known to lead to weight loss and is considered metabolically healthy; however there are conflicting reports on its effect on hepatic insulin sensitivity. KD fed animals appear metabolically healthy in the fasted state after 3 days of dietary challenge, whereas obesogenic high‐fat diet (HFD) fed animals show elevated insulin levels. A glucose challenge reveals that both KD and HFD fed animals are glucose intolerant. Glucose intolerance correlates with increased lipid oxidation and lower respiratory exchange ratio (RER); however, all animals respond to glucose injection with an increase in RER. Hyperinsulinaemic–euglycaemic clamps with double tracer show that the effect of KD is a result of hepatic insulin resistance and increased glucose output but not impaired glucose clearance or tissue glucose uptake in other tissues.